Study on the Complex Angle in Normed Spaces - Thürey, Volker W. (Newest Updates in Physical Science Research Vol. 9, 2021)
We consider a generalized angle in complex normed vector spaces. Its definition corresponds to the definition of the Euclidean angle in real inner product spaces. Not surprisingly it yields complex values as ‘angles’. This ‘angle’ has some simple properties, which are known from the usual angle in real inner product spaces. To do ordinary Euclidean geometry real angles are necessary. We show that even in a complex normed space there are many pure real valued ‘angles’. The situation improves yet in inner product spaces. There we can use the theory of orthogonal systems to find many pairs of vectors with real angles, and to do geometry which is based on principles which are already known by the Greeks 2000 years ago.